2016
DOI: 10.1071/an15365
|View full text |Cite
|
Sign up to set email alerts
|

A universal equation to predict methane production of forage-fed cattle in Australia

Abstract: Abstract. The methods for estimating methane emissions from cattle as used in the Australian national inventory are based on older data that have now been superseded by a large amount of more recent data. Recent data suggested that the current inventory emissions estimates can be improved. To address this issue, a total of 1034 individual animal records of daily methane production (MP) was used to reassess the relationship between MP and each of dry matter intake (DMI) and gross energy intake (GEI). Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
138
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(185 citation statements)
references
References 34 publications
28
138
5
1
Order By: Relevance
“…The prediction of MY value for Australian beef cattle on non-grain diets measured in chambers in Eqn 4, derived from an analysis of global MY data, was 21.85 + 0.77 + d_breed (0, 1, 2, average of 0.35) + 3.76 -3.37 = 23.4. This is 2.7 g/kg DMI higher than the MY value of Charmley et al (2016). Charmley et al (2016) noted that MP and DMI variances increase as MP and DMI levels increase while their coefficient of variance remain steady.…”
Section: Other Methane Meta-analysesmentioning
confidence: 89%
See 4 more Smart Citations
“…The prediction of MY value for Australian beef cattle on non-grain diets measured in chambers in Eqn 4, derived from an analysis of global MY data, was 21.85 + 0.77 + d_breed (0, 1, 2, average of 0.35) + 3.76 -3.37 = 23.4. This is 2.7 g/kg DMI higher than the MY value of Charmley et al (2016). Charmley et al (2016) noted that MP and DMI variances increase as MP and DMI levels increase while their coefficient of variance remain steady.…”
Section: Other Methane Meta-analysesmentioning
confidence: 89%
“…However, they found that the best methane-prediction model for North American lactating dairy-cow studies (modified from Nielsen et al 2013) was different than the best model for European, Australian and New Zealand studies (Yan et al 2000). Charmley et al (2016) analysed a total of 1034 individual animal records of MP to re-assess the relationship between MP and DMI. Data were restricted to trials conducted in the past 10 years using respiration chambers, with cattle fed forage-based diets (forage >70%).…”
Section: Other Methane Meta-analysesmentioning
confidence: 99%
See 3 more Smart Citations